Autophagy Induced by CX-4945, a Casein Kinase 2 Inhibitor, Enhances Apoptosis in Pancreatic Cancer Cell Lines. Issue 4 (April 2017) - Hwang, Dae Wook; So, Kwang Sup; Kim, Song Cheol; Park, Kwang-Min; Lee, Young-Joo; Kim, Sun-Whe; Choi, Chang-Min; Rho, Jin Kyung; Choi, Yun Jung; Lee, Jae Cheol
Abstract : Objectives: Pancreatic cancer is the most lethal malignancy with only a few effective chemotherapeutic drugs. Because the inhibition of casein kinase 2 (CK2) has been reported as a novel therapeutic strategy for many cancers, we investigated the effects of CK2 inhibitors in pancreatic cancer cell lines. Methods: The BxPC3, 8902, MIA PaCa-2 human pancreatic cancer cell lines, and CX-4945, a novel CK2 inhibitor, were used. Autophagy was analyzed by acridine orange staining, fluorescence microscope detection of punctuate patterns of GFP-tagged LC3 and immunoblotting for LC3. Cell survival, cell cycle, and apoptosis analysis was performed. Results: CX-4945 induced significant inhibition of proliferation and triggered autophagy in pancreatic cancer cells. This suppression of proliferation was caused by the direct inhibition of CK2 α, which was required for autophagy and apoptosis in pancreatic cancer cells. CX-4945 suppressed cell cycle progression in G2/M and induced apoptosis. The inhibition of CX-4945–induced autophagy was rescued by 3-methyladenine or small interfering RNA against Atg7, which attenuated apoptosis in pancreatic cancer cells. Conclusions: CX-4945, a potent and selective inhibitor of CK2, effectively induces autophagy and apoptosis in pancreatic cancer cells, indicating that the induction of autophagy by CX-4945 may have an important role in the treatment of pancreatic cancer.